A SELECT BIBLIOGRAPHY OF MUSIC IN AFRICA, by L. P. J. GASKIN, compiled at the International African Institute, under the direction of Professor K. P. Wachsmann, Institute of Ethnomusicology, African Studies Centre, University of California, Los Angeles. London International African Institute (1965). 83 pp. (45/. net). - Briegler, Ann (International Library of African Music, 1965)
pages: 85-86
Keywords: African Music